Case report: Rare floating gallbladder torsion in a child - Ren, Haiyang; Liu, Hao; Liu, Xiurui; Wei, Hua; Tian, Ping (Frontiers in Medicine, 2024)
Gallbladder Torsion (GT) refers to serious biliary emergencies caused by the torsion of the gallbladder on its mesentery along the axis of the cystic duct and cystic artery. It is very rare, especially in children. The clinical data of a child with floating gallbladder torsion who was treated in our hospital on March 14, 2024, were analyzed. A 6-year-old girl presented with abdominal pain and vomiting. Physical examination showed a mass in the right middle abdomen. Laboratory tests showed normal liver biochemical function and white blood cells. The benign lesion was considered by color Doppler ultrasound and CT, and the floating torsion of the gallbladder was diagnosed by MRCP and laparoscopic exploration. The child was treated with laparoscopic cholecystectomy (LC) and recovered well after the operation.